Pulmonary arterial hypertension and renal impairment in patients from the National Institute of Cardiology Dr. Ignacio Chávez, Mexico - Colon, Franklyn (2021)
Objective. The objective of the study was to describe the clinical characteristics and the evolution of the severity of pulmonary arterial hypertension (PAH) and the degree of renal failure. Material and methods. A retrospective observational study was carried out in which the physical and electronic medical records of 60 patients older than 18 years with a diagnosis of pulmonary arterial hypertension were analyzed. Results. In our study, 11.4% of the severe PAH group worsened renal function at six months, and 13.6% of the participants worsened it at one year. In contrast, in the group with moderate PAH, 18.8% worsened at six months, and 12.5% worsened at one year. Also, the GFR at one year was 54.15 mL/min/1.73 m2 in the moderate PAH group and in the severe PAH group was 73.55 mL/min/1.73 m2. Conclusion. The results of this research suggest that the deterioration of kidney function is related to the severity of pulmonary arterial hypertension.